Das an Electric Current have an Acoustic Component? - , A.A.Berezin (Journal of Energy Conservation, 2019)
The quantum model of electric current suggested by Feynman has been enlarged by n difference-differential Hamiltonian equations describing the phonon dynamics in one dimensional crystallyne lattice. The process of interaction between the electron and phonon components in a crystalline lattice of a conductor has been described by 2n parametrically coupled difference-differential Hamiltonian equations. Computer analysis of the system of these coupled equations showed that their solutions represent a form of the quantum recurrence similar to the Fermi-Pasta-Ulam recurrence. The results of the research might reconsider the existing concept of electric current and will be possibly helpful in developing an acoustic «laser».
Keywords: Electric Current; Phonons; Crystalline Lattice; Hamiltonian Equations; Electron-Phonon Interaction; Fermi-Pasta-Ulam Recurrence